(untitled) (Amsterdam, Netherlands, 2005)
This book lays out the argument for KM as a separate academic discipline, with its own body of knowledge (theoretical constructs), guiding principles, and professional society. In creating an academic discipline, there has to be a widely accepted theoretical construct, arrived at by undergoing scholarly scientific investigation and accompanying rigor. This construct becomes the basis for an academic curriculum, and proven methodologies for practice. Thus, the chapters in this book bridge theory and practice, providing guiding principles to those embarking on or evaluating the merits of a KM program. As a methodology itself for undertaking the development of a body of knowledge, a KM Research Map was developed to guide scholars, researchers, and practitioners. This book presents this map, and showcases cutting-edge scholarship already performed in this nascent field by including the dissertation results of eleven KM scholar/practitioners
Keywords: Knowledge management,Knowledge management,Universities and colleges,Quản lý tri thức,Quản lý tri thức,Đại học và trung học; Study and teaching,Research,Dạy và học,Nghiên cứu